'They call 'im Crowie': an investigation of the Aboriginal significance attributed to a wrecked River Murray barge in South Australia. (25th November 2016) - Roberts, Amy; van Duivenvoorde, Wendy; Morrison, Michael; Moffat, Ian; Burke, Heather; Kowlessar, Jarrad; Naumann, John; ,
Abstract : The Indigenous intangible heritage related to wrecked vessels has been poorly studied and documented. This article provides a counter to dominant maritime archaeology discourses via the investigation of the Aboriginal significance attributed to a wrecked and submerged River Murray barge ( Crowie ) in South Australia. There are numerous layers of Aboriginal significance that may be attributed to Crowie including the relationship of the community with their 'underwater country', Indigenous contributions to the riverboat industry, and the use of Aboriginal terms in vessel‐naming practices. Geophysical data from multibeam and sidescan sonar surveys allowed for confirmation of the proposed location of the wreck and through comparison with historical descriptions and photographs provided evidence to substantiate the assignation of the wreck as the Crowie barge.